Homoimplante de costela conservada em solução supersaturada de açúcar a 300% ou em açúcar in natura na reconstituição experimental de costelas em gatos (Felis catus) - Pedrozo, Josaine Cristina da Silva Rappeti (2006)
The fact that the animals had been living with the man favor the occurrence of accidents and traumas, as when they walk in streets our are subject to physical aggression as car accidents, falls, bites and gun fire, among others. The objective of this study was to evaluate the use of a bone homologous implant preserved in 300% sugar solution or sugar in natura for reconstitution of the thoracic wall in cats, involving three ribs. A costal defect was made in the right side of the thoracic wall in 16 adult cats and the ribs were used as homologous bone implants for correction of the defect. The preserved ribs were fixed to the receptor placed by means of a catheter needle. The animals were clinically evaluated by Xrays, histology, microbiological tests, tyhoracoscopy and movement of the costal arch by cinemetry. The evaluations were made in the pre-operative period and at 28, 45, 60, 90 and 120 days after surgery. The percentual of implant incorporation at 60 days was 91.67% in the group in which sugar in natura was used and 73.91% in the group using sugar at 300%. A mild reabsorption was observed at different times, 29.17% in the group in which in natura sugar was used and 37.79% in the group using sugar at 300%. No case of infection or rejection was observed in the period evaluated. In the microbiological culture, bacteria were found in the implants, and in the preserved media at a level of 10-2, compatible with the abcense of infection as well as non administration of antibiotics. Evaluation by cinemetry was carried out before the procedure and at 60 and 120 days after surgery, indicating a decrease in rib movement. It was concluded that the rib bone homologous implant preserve in sugar in natura or in a 300% solution is an option for reconstitution of costal wall in cats.